Experimental and numerical research on thermal performance of a novel thermal energy storage unit with phase change material. (5th March 2021) - Lin, Wenzhu; Ling, Ziye; Fang, Xiaoming; Zhang, Zhengguo
Highlights: A novel spiral tubes heat exchanger with PCM was designed. The thermal performance of this novel spiral tubes heat exchanger was investigated. Results indicated that the novel energy storage unit has good thermal performance. Abstract: This study experimentally and numerically investigates the thermal performance of a novel spiral-tube heat exchanger latent heat thermal energy storage unit. The shell side of the heat exchanger was filled with sodium acetate trihydrate (SAT) as the energy storage medium. Water was the heat transfer fluid (HTF) and flowed into the spiral tubes to charge or discharge the system. The outlet temperature of water, working power and energy of the system as well as the heat transfer coefficient and heat transfer area, were estimated to evaluate the thermal performance of this energy storage unit. The experimental analyses revealed that the recovered energy of the system during the discharging process ranged from 12.67 to 15.23 MJ with an average power higher than 2 kW for most of the process. The heat transfer coefficient and heat transfer area ranged from 72 W/K to 83 W/K for flow rates of 100 L/h to 500 L/h. Further, a numerical model was built and validated to investigate the phase change behavior more intuitively. The novel energy storage unit has the advantages of having a compact structure and multi-stream heat transfer capacity, which can offer a high heat transfer area per unit volume and ensure heat exchange of multiple working fluids.